THE INFLUENCE OF COMPENSATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF SOPPENG REGENCY PUBLIC WORKS AND SPATIAL PLANNING DEPARTMENT EMPLOYEES - Renggi Karendra; Anwar, Nurul Fadilah Aswar, Abdi Akbar Idris, Burhanuddin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to determine the effect of compensation and work environment on the performance of public works department employees and spatial planning in Soppeng district. The variables in this research consist of compensation and work environment as independent variables and employee performance as the dependent variable. This type of research is associative quantitative which uses primary data. The population in this study was 78 employees of the Public Works and Spatial Planning Department of Soppeng Regency. The data collection technique was carried out by distributing questionnaires to employees. The data analysis technique uses multiple linear regression with the help of SPSS version 25 software. The results of this research show that compensation has a positive and significant effect on employee performance, the work environment has a positive and insignificant effect on employee performance, compensation and the work environment have a positive and significant effect on the performance of employees of the public works department and spatial planning of Soppeng district.